Rational Design of Fluorescent/Colorimetric Chemosensors for Detecting Transition Metal Ions by Varying Functional Groups - Jong-Kwon Park; Junhyeop Shin; Seohyeon Jang; Myeong-Lok Seol; Jihyeon Kang; Seyoung Choi; Hojong Eom; Ohhyun Kwon; Soomin Park; Dong-Youn Noh; Inho Nam (Inorganics, 2022)
In recent decades, concerns about increasing biological and environmental contamination have necessitated the development of chemosensors with high selectivity, sensitivity, and cost-effectiveness. In principle, the sensing performance can be affected by the functional group(s) of receptor, the charge of the metal ion(s), and the electron configuration of the sensing molecule(s)e and metal ion(s). Fine controlling of the substituents can influence the electron density of the receptor to enhance the binding affinity to metal ions, which is an effective way to improve the photophysical properties of the sensors. This review explores the effect of functional group modification on the performance of various chemosensors represented by Pt(dithiolene)-based complexes (2012–2021). Then, recently developed Schiff base chemosensors (2014–2021) are discussed. The Schiff base is a good platform for controlling electron configuration due to a facile synthesis of various organic structures (aldehyde or ketone groups with primary amine derivatives). The discussion focuses on the detection type, physicochemical and optical properties, and applications of these chemosensors.